Does the "boost for mathematics" boost mathematics? A large-scale evaluation of the "lesson study" methodology on student performance - Erik Grönqvist; Björn Öckert; Olof Rosenqvist (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2021)
Students in East-Asian countries consistently score in the top in international assessments. One possible explanation for this success is their use of 'Lesson study' to enhance teaching practices, but evidence on its effectiveness is still scant. We evaluate a national teacher development program in Sweden - the 'Boost for Mathematics' - containing core elements of Lesson study, including weekly peer group meetings with an external tutor for an entire academic year. Exploiting the gradual roll-out of the program across compulsory schools, we find that it improves teaching practices and boosts students' mathematics performance. The positive effect on student performance persists also long after the intervention has ended. In addition, we show that the program passes a cost-benefit test. The educational strategies of Asian countries can, thus, be successfully modified and adapted to Western contexts by national policy.
Keywords: I21; J45; I28; 330; Teacher development; Student performance; Mathematics; Lesson study